A methods engineering study on the Pinatubo Ash Production System of the Tel Manila Inc. - Buenaventura, Luis III R. (College of Engineering, 2000)
Tel Manila Inc., an exporting company situated in Pasig, was selected as the site wherein a study which aims to focus on methods' improvement was conducted. Systems Documentation which uses the actual plant visits as the basis was presented with the application of the tools learned in the methods engineering class. Different problems have been identified using the Streamline Diagnosis and Ishikawa Diagram. The verified cause problems are the following : inefficient worker, hiring of unskilled worker, poor plant layout. With the cause problems, different alternatives were then formulated. For each cause problem, there were two alternatives. Hiring regular workers and revisions on the current operation of production were proposed for the 'Inefficient Worker' problem. On the other hand, conducting workshops and hiring skilled workers were cited for the second. Finally, for the problem regarding poor layout, addition of second floor and merging of the separate storage area were suggested. With the careful evaluation of the said alternatives, the group have been able to make a decision. A decision which suggests the most appropriate alternatives. Those that may provide great benefits yet utilize less cost.